A small-molecule inhibitor of UBE2N induces neuroblastoma cell death via activation of p53 and JNK pathways - Cheng, J (Nature Publishing Group, 2014)
Neuroblastoma (NB) is the most common extracranial neoplasm in children. In NB, loss of p53 function is largely due to cytoplasmic sequestration rather than mutation. Ubiquitin-conjugating enzyme E2 N (UBE2N), also known as Ubc13, is an E2 ubiquitin-conjugating enzyme that promotes formation of monomeric p53 that results in its cytoplasmic translocation and subsequent loss of function. Therefore, inhibition of UBE2N may reactivate p53 by promoting its nuclear accumulation. Here, we show that NSC697923, a novel UBE2N inhibitor, exhibits potent cytotoxicity in a panel of NB cell lines evidenced by its ability to induce apoptosis. In p53 wild-type NB cells, NSC697923 induced nuclear accumulation of p53, which led to its increased transcriptional activity and tumor suppressor function. Interestingly, in p53 mutant NB cells, NSC697923 induced cell death by activating JNK pathway. This effect was reversible by blocking JNK activity with its selective inhibitor, SP600125. More importantly, NSC697923 impeded cell growth of chemoresistant LA-N-6 NB cell line in a manner greater than conventional chemotherapy drugs doxorubicin and etoposide. NSC697923 also revealed in vivo antitumor efficacy in NB orthotopic xenografts. Taken together, our results suggest that UBE2N is a potential therapeutic target in NB and provide a basis for the rational use of UBE2N inhibitors like NSC697923 as a novel treatment option for NB patients.